ANALISIS KINERJA DALAM PENGEMBANGAN KAPASITAS RELAWAN (STUDI KASUS PADA PMI KABUPATEN WONOGIRI) - Prasetyo, Aji; Ahmad Husin; Elida Zia'ul Huda (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of training and education (X1), organizational support (X2), and volunteer experience (X3) on volunteer performance (Y) at the Indonesian Red Cross (PMI) in Wonogiri Regency. A survey was conducted among 30 active volunteers using a Likert-scale questionnaire, and the data were analyzed using multiple linear regression. The results indicate that only volunteer experience (X3) has a statistically significant effect on performance (coefficient = 0.688, p = 0.000), while training and education (X1) (coefficient = 0.155, p = 0.233) and organizational support (X2) (coefficient = 0.037, p = 0.747) do not show a significant influence. However, when considered simultaneously, the three independent variables have a significant joint effect on volunteer performance (F = 34.536, p = 0.000, R² = 0.799). Keywords: volunteer performance, training and education, organizational support, volunteer experience, Indonesian Red Cross (PMI) Wonogiri Regency.